A window on disease pathogenesis and potential therapeutic strategies: molecular imaging for arthritis. - Gompels, L; Paleolog, E (2011)
Novel molecular imaging techniques are at the forefront of both preclinical and clinical imaging strategies. They have significant potential to offer visualisation and quantification of molecular and cellular changes in health and disease. This will help to shed light on pathobiology and underlying disease processes and provide further information about the mechanisms of action of novel therapeutic strategies. This review explores currently available molecular imaging techniques that are available for preclinical studies with a focus on optical imaging techniques and discusses how current and future advances will enable translation into the clinic for patients with arthritis.